PENGARUH PEMBERIAN TERAPI MUSIK RELIGI TERHADAP PENURUNAN TINGKAT STRES PADA REMAJA (USIA 16-18 TAHUN) DI PANTI ASUHAN PANCASILA YAYASAN SUMBER PENDIDIKAN MENTAL AGAMAALLAH (SPMAA) DESA TURI KECAMATAN TURI KABUPATEN LAMONGAN - Saifudin, Moh.; Aisyiyah, Nasyiatul (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Stress is a condition of physical and psychological pressure due to the demands of the self and environment. This study aimed to determine the effect of music therapy Decreased stress levels Against Religious Youth (age 16-18 years) in the orphanage Pancasila Mental Education Fondation Source Religion og God (SPMAA) Pueblo district Turi Lamongan.Design of this research is the previous experiment design usinga pretest group – Final exam.this research is the previous experiment design using a pretest group - Final exam. The sampling method is simple random sampling. Samples are taken from 45 respondents. The research data is taken using the attached questionnaire.Once tabulated data is analyzed using the Wilcoxon test with significance level of p <0.0.5.The results shous that pretreatment of relious music more than most teenagers 26 (59 %) exexperienced mild stress levels. Although religious music therapy after 29 adolescents (65.9%) experienced a change in stress levels become normal. From the results of statistical tests results obtaine an influence of religious music therapy to reduce stress level with significant value Sign P = 0.000.Based on the research of religious music therapy is effective in reducing stress levels and is expected to health workers in the development of religious music therapy to cope with stress.Keywords: Religious Music Therapy, Stress Levels